A circadian clock in Neurospora crassa functions during plant cell wall deconstruction. Issue 5 (May 2020) - Díaz, Rodrigo D.; Larrondo, Luis F.
Abstract: Circadian clocks are autonomous timers that are believed to confer organisms a selective advantage by enabling processes to occur at appropriate times of the day. In the model fungus Neurospora crassa, 20–40 % of its genes are reported to be under circadian regulation, as assayed in simple sugar media. Although it has been well-described that Neurospora efficiently deconstructs plant cell wall components, little is known regarding the status of the clock when Neurospora grows on cellulosic material, or whether such a clock has an impact on any of the genes involved in this process. Through luciferase-based reporters and fluorescent detection assays, we show that a clock is functioning when Neurospora grows on cellulose-containing wheat straw as the only carbon and nitrogen source. Additionally, we found that the major cellobiohydrolase encoding gene involved in plant cell wall deconstruction, cbh-1, is rhythmically regulated by the Neurospora clock, in a manner that depends on cellulose concentration and on the transcription factor CRE-1, known as a key player in carbon-catabolite repression in this fungus. Our findings are a step towards a more comprehensive understanding on how clock regulation modulates cellulose degradation, and thus Neurospora 's physiology.